Rancang Bangun Sistem Informasi Persediaan Beras Pada CV Santri Abadi Indonesia - Aprilia Pramudita; Eko Purwanto; Hartono Hartono (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2026)
CV Santri Abadi Indonesia faces challenges in recording rice inventory manually, causing various problems such as delays in recording, the risk of data loss, and suboptimal inventory monitoring. The purpose of this scientific study is to design and build a rice inventory information system that can replace the manual recording process. This study applies the First In First Out (FIFO) approach in managing incoming and outgoing goods in a structured manner, and integrates the waterfall method as a system development model that includes the stages of analysis, design, implementation, testing, and maintenance. The results of this study prove that the information system built is able to provide direct inventory information, optimize the recording process, and improve cooperation between departments within the company. In addition, the application of the FIFO method helps ensure a more orderly distribution of rice according to the order of incoming goods. Based on this, the designed and developed information system can be a solution to overcome inventory management problems and support operational performance improvements at CV Santri Abadi Indonesia.